Environmental management of energy from biofuels and biofeedstocks - Speight, James G. (Energy and environment book series, 2014)
This is the most comprehensive and thorough volume on the environmental aspects of energy from biofuels and biofeedstocks. Biomass is a renewable resource whose utilization has received great attention due to environmental considerations and the increasing demands of energy worldwide. Since the energy crises of the 1970s, many countries have become interested in biomass as a fuel source to expand the development of domestic and renewable energy sources, reduce the environmental impacts of energy production, provide rural prosperity for its poor farmers, and bolster a flat agricultural sector.